2010
DOI: 10.1111/j.1467-7717.2010.01210.x
|View full text |Cite
|
Sign up to set email alerts
|

Addressing symptoms but not causes: stabilisation and humanitarian action in Timor‐Leste

Abstract: Asia's newest nation--Timor-Leste--has an unenviable track record of two Australian-led military stabilisation missions, five United Nations (UN) missions, and a vast humanitarian and international response over the course of the past decade. Two distinct approaches to stabilisation can be observed on this small half-island. The first is a 'security-first' approach, where development activities are complementary and serve to support security sector assistance, while the second emphasises traditional developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…It also remains unclear how integrated this system is in practice as the actual ability to integrate support provided to a specific sector and to the country overall is easier to aspire to than achieve. If we take the security sector during the two Australian-led military stabilisation missions as an example, the experience in Timor-Leste was for coordination at a 'soft' strategic level through regular information-sharing with section heads at the Australian Embassy in Dili, and so programmes remained siloed in focus with little depth of coordination amongst them [24]. To consolidate an integrated disaster response architecture in Timor-Leste it is important to plan ahead and obtain buy-in from the stakeholders for it to gain traction and not be rendered a superficial enterprise.…”
Section: Government's Role In Emergency Situationsmentioning
confidence: 99%
“…It also remains unclear how integrated this system is in practice as the actual ability to integrate support provided to a specific sector and to the country overall is easier to aspire to than achieve. If we take the security sector during the two Australian-led military stabilisation missions as an example, the experience in Timor-Leste was for coordination at a 'soft' strategic level through regular information-sharing with section heads at the Australian Embassy in Dili, and so programmes remained siloed in focus with little depth of coordination amongst them [24]. To consolidate an integrated disaster response architecture in Timor-Leste it is important to plan ahead and obtain buy-in from the stakeholders for it to gain traction and not be rendered a superficial enterprise.…”
Section: Government's Role In Emergency Situationsmentioning
confidence: 99%
“…A policy is only as good as the disposition and skills of the persons charged with implementing it. 14 Nevertheless, the 2007 parliamentary and presidential elections took place without any major incidents, despite the politically volatile situation associated with growing tensions within the security institutions, which eventually set the context for the attempted murders of President Ramos-Horta and Prime-Minister Xanana Gusmão on February 2008. 15 The swift normalization after the instability that these events generated, showed that the underlying situation was more stable and predictable, allowing 'UNMIT [to continue] its "one United Nations system" approach, consistent with its integrated strategic framework'.…”
Section: United Nations: Building the Peacementioning
confidence: 99%
“…Still, as Lothe and Peake argue, '[in] Timor-Leste, as elsewhere, stabilisation has proven unable to contend with the "underlying" causes or drivers of conflict, including persistent political cleavages, ethnic and community divisions, and social and economic inequalities'. 20 The holding of free and fair elections, though constituting a positive signal, is not sufficient to assure a democratic path. 21 The new government after the parliamentary elections of 2012 faces the task of controlling corruption and putting in place an inclusive reform programme.…”
Section: United Nations: Building the Peacementioning
confidence: 99%
“…Preliminary standards for monitoring and evaluation determined that over half of police units were incapable of undertaking traditional police responsibilities. 54 Yet, without a formalized, legitimized function to reveal this discrepancy, the PNTL was permitted to take on responsibilities without evaluation of their readiness. The UN mission failed to establish an evaluation and monitoring wing to oversee police development; the host-nation did not have the expertise or willpower to establish one on its own.…”
Section: Robust Vetting Of Security Forcesmentioning
confidence: 99%